2011
DOI: 10.1021/ja108820s
|View full text |Cite
|
Sign up to set email alerts
|

CORM-3 Reactivity toward Proteins: The Crystal Structure of a Ru(II) Dicarbonyl−Lysozyme Complex

Abstract: CORM-3, [fac-Ru(CO)(3)Cl(κ(2)-H(2)NCH(2)CO(2))], is a well-known carbon monoxide releasing molecule (CORM) capable of delivering CO in vivo. Herein we show for the first time that the interactions of CORM-3 with proteins result in the loss of a chloride ion, glycinate, and one CO ligand. The rapid formation of stable adducts between the protein and the remaining cis-Ru(II)(CO)(2) fragments was confirmed by Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES), Liquid-Chromatography Mass Spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
217
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(238 citation statements)
references
References 23 publications
9
217
0
3
Order By: Relevance
“…Although previous work has shown that iCORM-3 has much less effect than CORM-3 on biological material (8,17,34,37), very little has been done to elucidate bacterial viability with, and specific responses to, iCORM-3. The data presented herein show that iCORM-3 (made via incubation of CORM-3 in PBS) has virtually no effect on the growth of E. coli, whereas at the same concentration, CORM-3 readily inhibits growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although previous work has shown that iCORM-3 has much less effect than CORM-3 on biological material (8,17,34,37), very little has been done to elucidate bacterial viability with, and specific responses to, iCORM-3. The data presented herein show that iCORM-3 (made via incubation of CORM-3 in PBS) has virtually no effect on the growth of E. coli, whereas at the same concentration, CORM-3 readily inhibits growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This process is thought to allow CORM-3 to release the labile CO, which escapes into the gas phase upon bubbling, leaving a CO-depleted iCORM-3 compound in solution (8). However, mounting literature suggests that CORM-3 is unable to release large quantities of CO under these conditions; rather, the carbonyl compound is altered forming a stable molecule that releases CO with a much slower rate (13,28,37). This inactivation process could produce a very slow CO-releasing tricarbonyl complex (22) or a dicarbonyl compound, which is formed via the release of CO 2 from CORM-3 (37).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact the original purpose for which amino acids containing an azide group has been designed was "click" chemistry, and consequently one may also add metal-carbonyl complexes with even stronger C≡O bands to it in a post-translational coupling step as a second alternative [48]. Finally, Re-carbonyl or Ru-carbonyl complexes have been bound selectively to histidines [30,[56][57][58].…”
Section: Advancing the Selectivitymentioning
confidence: 99%